Developmental change in the calcium sensor for synaptic vesicle endocytosis in central nerve terminals - Smillie, Karen J. (2005)
Synaptic vesicle endocytosis is stimulated by calcium influx in mature central nerve terminals via activation of the calcium-dependent protein phosphatase calcineurin. However in different neuronal preparations calcineurin activity is either inhibitory, stimulatory or irrelevant to the process. We addressed this inconsistency by investigating the requirement for calcineurin activity in synaptic vesicle endocytosis during development, using vesicle recycling assays in isolated nerve terminals. We show that endocytosis occurs independently of calcineurin activity in immature nerve terminals, and that a calcineurin requirement develops two to four weeks after birth. Calcineurin-independent endocytosis is not due to the absence of calcineurin activity, since calcineurin is present in immature nerve terminals and its substrate dynamin I is dephosphorylated on depolarisation. Calcineurin-independent endocytosis is calcium-dependent, since substitution of the divalent cation barium inhibits the process. Finally we demonstrated that in primary neuronal cultures derived from neonatal rats, endocytosis that was initially calcineurin-independent developed a calcineurin requirement on maturation in culture. Our data account for the apparent inconsistencies regarding the role of calcineurin in synaptic vesicle endocytosis, and we propose that an unidentified calcium sensor exists to couple Ca(2+) influx to endocytosis in immature nerve terminals.